Reframing Cybersecurity Risk in Social Media through Digital Intimacy and Relational Exposure - Khairati, Fajrul; Putra, Hasdi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Cybersecurity research has traditionally focused on technical vulnerabilities, malicious attacks, and organizational safeguards to protect digital infrastructure. Although socio-technical perspectives have gained attention, everyday digital practices remain insufficiently examined as sources of cybersecurity risk. Concurrently, social media platforms have normalized digitally mediated intimacy, including public displays of affection (digital PDA), which embed emotionally salient and relational data into platform-based information systems. These practices introduce exposure mechanisms that are not adequately captured by conventional, technically bounded, and intent-based cybersecurity models. This article reframes cybersecurity risk by conceptualizing digital PDA as a distinct form of behavioural and relational exposure. Through an integrative conceptual synthesis of cybersecurity risk management, behavioural cybersecurity, and digital intimacy literature, the study demonstrates that digital PDA differs fundamentally from general digital oversharing. Digital PDA is relationally embedded, emotionally driven, cumulative over time, and amplified by platform affordances such as algorithmic recommendation, data persistence, and content resurfacing. As a result, intimacy-driven disclosures generate exposure that extends beyond individual users and evolves independently of the original act of sharing. The article develops conceptual frameworks that position digital PDA across multiple cybersecurity risk domains, including human, procedural, platform, and governance risks. By foregrounding relational exposure, this study advances behavioural cybersecurity beyond awareness and compliance-centric assumptions and contributes to information systems research by clarifying how platform design and governance shape cybersecurity risk. The findings provide a foundation for future empirical research and more context-sensitive cybersecurity and digital governance strategies in social media–driven environments.